THE ROLE OF PARENTS IN BOLO VILLAGE IN SUPPORTING DISTANCE LEARNING DURING THE COVID-19 PANDEMIC - ida mawaddah; Zulhafriliya Zulhafriliya; Sudarsono Sudarsono (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2021)
The Indonesian government was concerned about the impact of a wider spread of Covid-19, so it moved quickly to break the chain of transmission by urging people to live a healthy lifestyle, avoid crowds, and keep a safe distance. As a result, the circumstance has a significant impact on education and learning. The goal of this study is to learn more about the role of parents in promoting distant learning and to identify the characteristics that encourage and limit distance learning in Bolo Village during the Covid-19 outbreak. Students are forced to study from home due to government regulations. Teachers can ensure students' learning activities in a variety of ways, one of which is by involving parents as the primary companion of students when they are at home. The participants in this study were parents and their junior high school-aged children. The information was gathered through organized interviews utilizing the researcher's prepared questions. The data in this study was analyzed utilizing qualitative data analysis approaches such as the Miles and Huberman model, which features a cycle that includes data reduction, data presentation, verification, and conclusion drafting. According to the findings of this study, parents in Bolo Village played four roles in supporting learning from home during the Covid-19 pandemic: 1) accompanying children in learning, 2) intense communication with children, 3) providing supervision to children, and 4) educating and supporting children motivation. The supporting variables discovered are: 1) responsibility, 2) family values, and 3) availability to satisfy the needs of children. There are also barriers, such as 1) internet network issues, 2) too much workload, and 3) boring and less diversified learning approaches.